2023
DOI: 10.21203/rs.3.rs-2769468/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive value of adipokines for the severity of acute pancreatitis: a meta-analysis 

Abstract: Background Severe acute pancreatitis (SAP) is a dangerous condition with a high mortality rate. Many studies have found an association between adipokines and the development of SAP, but the results are controversial. Therefore, we performed a meta-analysis of the association of inflammatory adipokines with SAP. Methods We screened PubMed, EMBASE, Web of Science and Cochrane Library for articles on adipokines and SAP published before March 2, 2023. The quality of the literature was assessed using QUADAS criteri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…According to the literature, there are many discovered adipokines so far (5-7). In the same way, Yu et al (17), Karpavicius et al (18) and Wos-Wroniewicz et al (19) reported adiponectin, IL-6, resistin, ghrelin, and leptin in AP. This review article summarizes the role of some other adipokines in AP, such as asprosin, apelin, adipsin, angiopoietin-like protein 2 (ANGPTL2), chemerin, FGF-21, progranulin, visfatin, vaspin, omentin-1, RBP4, lipocalin 2, TNF-a, and osteopontin (OPN) since these have not collectively summarized and reported yet.…”
Section: Zhang Et Al 2017 Tnf-amentioning
confidence: 68%
“…According to the literature, there are many discovered adipokines so far (5-7). In the same way, Yu et al (17), Karpavicius et al (18) and Wos-Wroniewicz et al (19) reported adiponectin, IL-6, resistin, ghrelin, and leptin in AP. This review article summarizes the role of some other adipokines in AP, such as asprosin, apelin, adipsin, angiopoietin-like protein 2 (ANGPTL2), chemerin, FGF-21, progranulin, visfatin, vaspin, omentin-1, RBP4, lipocalin 2, TNF-a, and osteopontin (OPN) since these have not collectively summarized and reported yet.…”
Section: Zhang Et Al 2017 Tnf-amentioning
confidence: 68%